Pengaruh Media Sosial, Teknologi Informasi dan Komunikasi, serta Inovasi Terhadap Keunggulan Bersaing: Studi Kasus pada UMKM Di Surakarta - Khusnul Khotimah; Ahmad Mardalis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of social media, information and communication technology (ICT), and innovation on competitive advantage among micro, small, and medium enterprises (MSMEs) in Surakarta. A quantitative approach was employed, using a survey method involving 186 MSME respondents. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that all three independent variables—social media, ICT, and innovation—have a positive and significant effect on competitive advantage. Among them, innovation emerged as the most dominant factor in enhancing competitive advantage, followed by ICT and social media. These findings highlight the importance of integrating these three elements into MSMEs' business strategies to remain resilient and competitive in the digital era.